"Know that you`re not just settling": Exploring women athletes` self-compassion, sport performance perceptions, and well-being around important competitive events - Adam, M. E. K.; Eke, A. O.; Ferguson, L. J. (Journal of Sport & Exercise Psychology, 2021)
Self-compassion, an adaptive self-attitude, is a resource that women athletes use during emotionally difficult times and as a way to reach their potential. The relationship between self-compassion and sport performance, however, is complex. The role and experience of self-compassion within perceived important competitive events are important to explore, as athletes face unique pressures and stressors in these meaningful sport experiences. This collective case study describes women athletes` self-compassion, sport performance perceptions, and well-being around a self-identified important competitive event. Competitive women athletes (N = 9) participated in two one-on-one interviews, before and after their important competitive event. Results from the holistic, functional, and thematic analyses are represented by holistic case descriptions and an overarching theme, Continuing to Excel in Sport, and subthemes, Reframing Criticism and A Determined Approach. In important competitive events, women athletes utilize self-compassion to promote performance perceptions and well-being when preparing, competing, and reflecting to excel in sport.